The effect of structural liquidity on performance in Polish commercial banks (measured with margin level) in 2009-2016 - Wójcik-Mazur, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of this article is to determine the impact of liquidity policy, which reflected mainly in the asset structure of Polish banks on the level of margin. The paper diagnoses the relationships between the levels of profitability (margin) generated by 4 biggest Polish commercial banks and their structural liquidity level. As an independent variable, the model design implied the level of margin, whereas liquidity risk predictors represented balance measures that identified the level of liquid assets, funding liquidity risk, share of loans in total assets and degree of involvement in the interbank market. The studies demonstrated that both the increase in liquid assets and the level of loans in total assets has a positive effect on the margin level. It means the rate of return of assets (include liquid assets) is still higher than cost of debt in Polish banks. However, it should be emphasized that the increasing contribution of the funding liquidity risk (measured as a ratio of loans to deposits) in the period of 2009-2016 was not accompanied by a statistically significant increase in the margin, which appears to be caused by the interest rate policy of the Polish central bank
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 295-308
Keywords: liquidity risk; banks; margin; ryzyko płynności; bank; marża